Photosubstitution of Monodentate Ligands from RuII–Dicarboxybipyridine Complexes - Caraballo, Rolando Manuel (2017)
We report the photophysical and photochemical properties of RuII–polypyridine complexes [Ru(bpy)(dcbpy)py2]2+ (1)2+ and [Ru(dcbpy)2py2]2+ (2)2+ (bpy = 2,2′-bipyridine, dcbpy = 4,4′-dicarboxy-2,2′-bipyridine, py = pyridine). These complexes combine a monodentate ligand with a chelate bipyridine substituted with carboxylate groups. At low pH, both complexes present metal-to-ligand charge transfer absorption bands in the visible region and room-temperature photoluminescence with long excited-state lifetimes (τ > 200 ns). At physiological pH, their absorption and emission maxima are displaced to higher energies, with a significant reduction of their emission lifetime. These species show photosubstitution of the monodentate pyridine upon irradiation at 450 nm. At low pH, the quantum yield for this process is very low, but at physiological pH, they are very active, with a φPS,450 value of 0.14 for (1)2+ and of 0.17 for (2)2+. The products of photosubstitution were identified as monoaquo complexes. Both the reactants and the products of the photosubstitution show photoluminescence, but with very different lifetimes, making it possible to monitor the reaction by the time constant of their decay. The ability of complexes (1)2+ and (2)2+ to photorelease monodentate ligands at physiological pH makes them attractive candidates for the delivery of biomolecules linked to more complex structures through the carboxylate functional group.